2019
DOI: 10.3390/ijms20051230
|View full text |Cite
|
Sign up to set email alerts
|

Cytarabine-Resistant FLT3-ITD Leukemia Cells are Associated with TP53 Mutation and Multiple Pathway Alterations—Possible Therapeutic Efficacy of Cabozantinib

Abstract: Internal tandem duplication of FLT3 juxtamembrane domain (FLT3-ITD)-positive acute myeloid leukemia (AML) leads to poor clinical outcomes after chemotherapy. We aimed to establish a cytarabine-resistant line from FLT3-ITD-positive MV4-11 (MV4-11-P) cells and examine the development of resistance. The FLT3-ITD mutation was retained in MV4-11-R; however, the protein was underglycosylated and less phosphorylated in these cells. Moreover, the phosphorylation of ERK1/2, Akt, MEK1/2 and p53 increased in MV4-11-R. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…The apoptotic effect of AraC is p53-dependent, since the FLT3-ITD leukemia cell line, which harbors mutant TP53, is AraC-resistant ( Ko et al, 2019 ). Perhaps AraC-induced autophagy is also p53-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic effect of AraC is p53-dependent, since the FLT3-ITD leukemia cell line, which harbors mutant TP53, is AraC-resistant ( Ko et al, 2019 ). Perhaps AraC-induced autophagy is also p53-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Although the removal of Ara-C results in a slight increase in STAT5 phosphorylation, the resistance of MV4-11R cells to this drug is not directly linked to overactivated STAT5. ERK1/2 and AKT kinases that also play a crucial role in cell survival, are involved in the resistance of MV4-11 cells to Ara-C [29]. It is then likely that Ara-C depletion may overexpress or overactivate these survival pathways in resistant MV4-11 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of MCL-1 has been shown in different cell lines with varying FLT3-ITD IS at the JMD (MOLM-13, MV4-11) or TKD1 level (32D, A627E variant) compared to FLT3 wildtype (RS4-11) [33]. Upregulated MCL-1 at the protein level was also detected in a cytarabine-resistant cell line MV4-11-R harboring the FLT3-ITD mutation at the JMD level [93]. In the FLT3-ITD variant A627E inserting at the TKD1 level, Breitenbuecher et al described upregulation of anti-apoptotic MCL-1 and showed sustained activation of ERK1/2 despite midostaurin-mediated inhibition of FLT3.…”
Section: Characterizing the Molecular Basis Of Chemotherapy And Tki R...mentioning
confidence: 93%